A Systematic Literature Review of Productive Zakat Models - Arif, Arif; Al Rieza, Irfaul Risqoh; Khadijah, Khadijah; Handoko, Lukman Hakim (International Journal of Zakat, 2024)
This research reviewed scholarly works on productive zakat models using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) technique. The data consisted of 68 articles, generated from Google Scholar database using the Publish or Perish software. Further data cleaning was performed, resulting in 22 articles for the final analysis. Four models of productive zakat were identified from the sample, i.e., empowerment and capital for MSMEs, capital for agricultural businesses, capital for livestock businesses, and educational entrepreneurship. Those productive zakat models were proven to effectively reduce poverty and increase social equality.